PERANCANGAN DEBRIEFING FORM BERBASIS WEB PADA PELAYANAN DI UNIT ATS REPORTING OFFICE PERUM LPPNPI CABANG DENPASAR - Mochammad Reyhan Hafiz; Lusiana Dewi Kusumayati; Yeni Rochmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Perum LPPNPI Denpasar Branch is one of the operators of Indonesian aviation navigation under the auspices of the State-Owned Enterprises. Perum LPPNPI Denpasar Branch which is located at I Gusti Ngurah Rai Airport Denpasar is located in the province of Bali. Debriefing form services in Denpasar still use paper manuals. The author designed this web so that reporting at Denpasar airport is more effective and can be developed further in the future. This study uses a Research and Development (R&D) research method. The data collection technique that the author took was based on observations for 5 months during On The Job Training at Perum LPPNPI Denpasar Branch and interviews with an ATS Reporting Office personnel. This web application contains various features in it such as the same reporting form as a paper manual, showing per reporting date, can be recapitulated in pdf form. And according to the author, it is very easy for ACO personnel and concerned to serve the Debriefing Form Reporting. The result of the research is the creation of a web-based Debriefing form with features that are quite complete and facilitate performance for ACO personnel and the parties concerned. It is hoped that in the future the Management at Perum LPPNPI Denpasar Branch can implement web-based debriefing reporting forms.